The Role of Bronchoscopy as a Diagnostic and Therapeutic Modality in Critically Ill Patients with Respiratory Failure and Pneumonia in the Intensive Care Unit: A Descriptive Observational Study - Edi Darmawan; Rizki Taufiqurrahman; Sutan Syarif Muda Dalimunthe; Septian Adi Permana; Arie Zainul Fatoni; Teuku Yasir; Andriamuri Primaputra Lubis; Rommy Fransiscus Nadeak; Bastian Lubis (Journal of Society Medicine, 2026)
Introduction: Respiratory failure remains a major cause of intensive care unit (ICU) admission and is associated with substantial morbidity and mortality worldwide. Pneumonia frequently results in respiratory failure requiring invasive mechanical ventilation. Bronchoscopy enables direct airway visualisation and bronchoalveolar lavage (BAL), providing important diagnostic and therapeutic benefits in critically ill patients. This study evaluated the role of bronchoscopy in ICU patients with pneumonia-associated respiratory failure. Methods: This descriptive observational study was conducted in the adult ICU of RSUP H. Adam Malik Medan, Indonesia. Adult patients with pneumonia-associated respiratory failure requiring invasive mechanical ventilation who underwent bronchoscopy during ICU treatment in December 2025 were included. Data were obtained from medical records, bronchoscopy reports, laboratory investigations, and radiological examinations. Outcomes included chest radiographic findings, leukocyte count, neutrophil-to-lymphocyte ratio (NLR), and BAL culture results. Results: Eighteen patients were included. Radiological improvement was observed in 13 patients (72%), whereas 5 patients (28%) demonstrated deterioration. Leukocyte count improvement occurred in 16 patients (89%), and NLR improvement was identified in 15 patients (83%). BAL cultures predominantly revealed Acinetobacter baumannii, followed by Klebsiella pneumoniae and Pseudomonas aeruginosa. Conclusion: Bronchoscopy provides important diagnostic and therapeutic benefits in ICU patients with pneumonia-associated respiratory failure by facilitating airway clearance, improving inflammatory parameters, and supporting targeted antimicrobial therapy.